Maternal Type 1 diabetes activates stress response in early placenta. (February 2017) - Gauster, Martin; Majali-Martinez, Alejandro; Maninger, Sabine; Gutschi, Elisabeth; Greimel, Patrick H.; Ivanisevic, Marina; Djelmis, Josip; Desoye, Gernot; Hiden, Ursula
Abstract: Introduction: Human pregnancy and in particular the first trimester, is a period highly susceptible towards adverse insults such as oxidative stress, which may lead to inadequate embryonic and feto-placental development. Diabetes mellitus is associated with increased oxidative stress caused by hyperglycemia, reactive oxygen species (ROS) production and inflammatory signals. In pregnancy, diabetes elevates the risk for early pregnancy loss, preeclampsia and fetal growth restriction, pathologies that origin from early placental maldevelopment. We hypothesized that maternal Type 1 diabetes mellitus (T1DM) induces oxidative stress in the first trimester human placenta. Methods: We quantified stress induced, cytoprotective proteins, i.e. heat shock protein (HSP)70 and heme oxygenase (HO)-1 and determined protein modifications as markers for oxidation and glycation, i.e. levels of 4-hydroxynonenal (HNE) or Nε-(carboxymethyl)lysine (CML) modified proteins. Moreover, we measured expression levels of enzymes involved in antioxidant defense in the first trimester (week 7–9) placenta of normal and T1DM women by immunoblot and real-time qPCR. Primary human trophoblasts were isolated from first trimester placenta and the effects of oxygen, hyperglycemia and the pro-inflammatory cytokine tumor necrosis factor (TNF)-α on levels of HSP70 and HO-1 were analyzed. Results: HSP70 (+19.9± 10.1%) and HO-1 (+63.5± 14.5%) were elevated (p < 0.05) in first trimester placenta of T1DM women when compared to normal women. However, levels of HNE or CML modified proteins were unchanged. Also, expression of most antioxidant enzymes was unchanged, with only superoxide dismutase 3 ( SOD3 ) being upregulated by 3.0-fold (p < 0.05). In isolated primary trophoblasts, HSP70 and HO-1 were upregulated by increasing oxygen tension, but not by hyperglycemia or TNF-α. Conclusion: Although protein oxidation and glycation was not elevated, we infer that T1DM increases placental cellular stress in the first trimester. Elevated stress in early placenta of T1DM women may contribute to disturbances in placental development. Highlights: Maternal T1DM upregulates stress responsive proteins in early placenta. We conclude that maternal T1DM increases cellular stress in early placenta. Cellular stress may contribute to the risk for pregnancy pathologies associated with T1DM.